Crianças em cena. Sobre mobilidade infantil, família e fluxos migratórios em Cabo Verde - Andréa de Souza Lobo (Ciências Sociais Unisinos)
This article is aimed at demonstrating that the universe of kinship in the Creole society of Cape Verde is not pre-defined, kinship relations are not irrevocable and free from the need for reiteration. Family relations are analyzed as a construction, a project which results from constant negotiations among its members. The central argument is that, in Cape Verde, family relations are characterized by mutual commitment, regular social contacts and an intra and inter-domestic flow of material and immaterial benefits. These requisites are fundamental for the construction of the feeling of proximity and strengthen pre-existing kinship bonds.